ANALISIS PELANGGARAN ETIKA BISNIS DALAM KASUS KORUPSI PT PERTAMINA: PERSPEKTIF ETHICAL LEADERSHIP - Nopriyan Mulyana; Yohannes Don Bosco Doho (Jurnal Ilmiah Manajemen dan Akuntansi, 2026)
This study aims to analyze business ethics violations in the corruption case involving crude oil and refinery product governance at PT Pertamina (Persero) for the period 2018–2023 through the lens of ethical leadership. This case represents one of the largest corruption scandals within Indonesia's state-owned enterprises, with estimated state losses reaching IDR 285,00 trillion. The study employs a qualitative approach with a case study design, utilizing secondary data obtained from publications by the Attorney General's Office, Pertamina's annual reports, credible national media, and academic journals. The analysis was conducted using the frameworks of Ethical Leadership, Bad Leadership, and Fraud Triangle Theory. The findings reveal failures in ethical leadership, weaknesses in organizational oversight, and conditions that enabled corrupt practices to occur. The impacts include state financial losses, a decline in the company's reputation, and a reduction in public trust. This study recommends strengthening governance, enhancing internal oversight, and building an integrity-based organizational culture to prevent the recurrence of similar cases.